Ann Yearsley, Earl Goodwin, and the Politics of Romantic Discontent - Foss, Chris (Romanticism on the Net)

(untitled) (Université de Montréal, 2018)
There is a dearth of more substantial critical studies on Ann Yearsley’s tragic drama Earl Goodwin in general, and while the few out there have helpfully illuminated the play’s representation of the historical plight of women and the poor during Anglo-Saxon times, as well as its application to their current predicaments in Romantic-era England and France, they have tended to leave unexplored the ways in which Yearsley simultaneously is clarifying and extending her anger at and frustration with the class- and gender-based discrimination she experienced firsthand in the fallout with her mentor Hannah More over the profits from her first book. This article aims to fill this gap by delineating the many ways in which Earl Goodwin represents, on one level, her ongoing response to the defamation she suffered in the wake of More’s public campaign to ruin her reputation. Documenting the inextricability of the play’s explicit social and political critiques with Yearsley’s ongoing response to the More fiasco should in fact reinforce the extent to which her more familiar initial reactions are as fundamentally politically as they are personally motivated. Earl Goodwin offers readers a positive example of how to respond to abuses of power without resorting to revenge while still actively resisting, always refusing to airbrush the inequities she and others like her (women, the poor, and especially working-class women) continue to face day in and day out, enduring insult and injustice, but remaining undaunted in the commitment to the cause of beneficial social change.